Analisis Faktor Produksi dan Efisiensi Alokatif Usahatani Kentang di Desa Sumberejo Kecamatan Ngablak Kabupaten Magelang Jawa Tengah - Novialno, Trias; Yuliawati, Yuliawati (Universitas Galuh, 2024)
Sumberejo village is located in Ngablak sub-district where most of the people work as potato farmers. Some of the problems faced by potato farmers are limited land area (X1), manure (X2), labor (X3), seeds (X4), and pesticides (X5). The purpose of this research is to analyze the effect of the use of production factors on potato production and analyze the efficiency of the use of production factors in potato farming. This research was conducted in Sumberejo Village, Ngablak Subdistrict, Magelang District from June to September 2023. The sampling technique used simple random method with 38 farmers as respondents. Data were collected by interview using a questionnaire. The dependent variable is potato production and the independent variables are land area (X1), manure (X2), labor (X3), seeds (X4) and pesticides (X5). The results showed that production factors that affect potato production in Sumberejo Village are labor (X3), seeds (X4), while land area (X1), manure (X2), and pesticides (X5) have no effect on potato production. The use of production factors of land area (X1), labor (X3), seeds (X4) and pesticides (X5) in potato farming in Sumberejo Village is not efficient, while the use of manure (X2) is inefficient.